Digital Signature Security Analysis By Applying The Elgamal Algorithm And The Idea Method - Rizka Khairani Lubis; A M H Pardede; Husnul Khair (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
The development of an all-digital era, all activities use digital technology. Including signatures, hands are no longer manual now, signatures can be modified digitally. The application of digital signatures can be used to allow for document authenticity issues. The signature combines two methods namely Elgamal Algorithm and IDEA. The Elgamal algorithm is used to encrypt and decrypt signatures. The IDEA algorithm is used to strengthen signatures so that others don't modify them. The signature process begins with generating the public and private keys. The process of generating public keys (p,q,g,y) and private keys. With the signature of a binary document that is given by the sender to the recipient, the authenticity of the contents of the file, the identity of the sender, and the files that have been received by the recipient can be guaranteed. Affixing a digital signature is done by encrypting it with the sender's private key. In this way, checking the authenticity of documents and senders can be done.